MEDIA REPRESENTATION OF FEMALE ATHLETES AT THE MOST “GENDER-EQUAL” OLYMPIC GAMES - Đukić Živadinović, Tatjana; Vujović, Marija (Sport - nauka i praksa, 2022)
The Tokyo 2021 Olympics are declared the first gender-equal games because almost 49% of the nearly 11,000 athletes in Tokyo were women, which is why they are very important for the analysis from the gender perspective. This paper aims to determine how much and in what way female athletes were represented in the media. The research is based on the hypothesis that female athletes are underrepresented compared to male athletes and that most media content about female athletes contains gender stereotypes. Quantitative and qualitative content analysis were applied. The corpus of research consists of a total of 730 articles published on the Serbian digital media "Blic Online". The authors conclude that only 30 percent of media space is dedicated to female athletes. The research also shows that 40 percent of articles about female athletes contain gender stereotypes or are not related to sports and professional results of female athletes. Despite the progress achieved in the Olympic Games' gender policy, the media image does not reflect it.
Keywords: Olympic Games; media; representation; gender; femail sport